2023
DOI: 10.3389/fmicb.2023.1139625
|View full text |Cite
|
Sign up to set email alerts
|

Effects from supplementary feeding of bamboo powder in perinatal period on farrowing process, serum biochemical indexes, and fecal microbes of sows and offspring piglets

Abstract: IntroductionThis study was conducted to explore the effects of supplementary feeding of bamboo powder on the physical parameters of sows during the perinatal period of 7 days ± in parturition, including farrow duration, serum biochemical indexes, fecal physicochemical indexes, and microbial flora.MethodsThirty pregnant sows were randomly divided into three groups: the control group was fed a basal diet, TRE1 group and TRE2 group were fed a basal diet supplemented with 30 g d−1 and 60 g d−1 bamboo powder, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 57 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…It was shown that serum total protein concentration increased significantly with the increase in dietary fiber supplementation level when adding citrus pulp, maize cob, and lucerne hay, which had a negative effect on production performance ( Bakare et al, 2016 ). Our previous study found that supplemental feeding of 30 g/day or 60 g/day bamboo powder in the diet of sows during the perinatal period had no significant effects on serum total protein and urea nitrogen of sows ( Dai et al, 2023 ), and similar results were obtained in this experiment. The above studies indicated that 2% BBF supplementation had no negative effects on the protein metabolism of sows during gestation and lactation.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…It was shown that serum total protein concentration increased significantly with the increase in dietary fiber supplementation level when adding citrus pulp, maize cob, and lucerne hay, which had a negative effect on production performance ( Bakare et al, 2016 ). Our previous study found that supplemental feeding of 30 g/day or 60 g/day bamboo powder in the diet of sows during the perinatal period had no significant effects on serum total protein and urea nitrogen of sows ( Dai et al, 2023 ), and similar results were obtained in this experiment. The above studies indicated that 2% BBF supplementation had no negative effects on the protein metabolism of sows during gestation and lactation.…”
Section: Discussionsupporting
confidence: 87%
“…Dietary fiber regulates serum fat metabolism. Our previous study showed that the serum triglyceride concentration and total cholesterol decreased significantly with the increase of bamboo powder from 0 g/day, 30 g/day, and 60 g/day in the diets of perinatal sows ( Dai et al, 2023 ). Another study in pregnant sows found that dietary supplementation with beet meal or bran significantly reduced serum total cholesterol in sows at 110 days of gestation ( Shang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dietary fiber is known to reduce fat accumulation and ameliorate obesity ( 44 ). The previous studies indicated that bamboo powder could reduce total cholesterol and triglyceride levels in the serum of sows ( 45 ), and sugar beet pulp and wheat bran could decrease serum cholesterol levels ( 46 ). This study showed that the addition of CSSF to sow diets reduced the levels of serum triglycerides, cholesterol and high-density lipoprotein cholesterol.…”
Section: Discussionmentioning
confidence: 99%